Serum CA 19.9 as a Tumour Marker in Colorectal Cancer Staging- An Experimental Study - Parveen, Monira; Md Badruddoza, Shah; Asafudullah, SM; Khanom, Khadiza; Sultana, Arefa; Akhter, Shameem (TAJ: Journal of Teachers Association, 2020)
This cross-sectional, descriptive observational study was carried out for a period of 24 months from January 2014 to December 2015 in the Department of Pathology and Department of Surgery, Rajshahi Medical College, Rajshahi for estimation of serum 19-9 level in total fifty four patients. Histopathological Staging was correlated with the preoperative values of serum CA 19-9 level. Data were collected by face to face interview, clinical examination and findings of laboratory investigations. Preoperative serum CA 19-9 levels were estimated by Enzyme Linked Immunosorbent Assay (ELISA) Method. The study revealed that the colorectal carcinoma was highest in the 5th and 6th decade and rectal area (46.3%) and male predominance was observed with male to female ratio being 3:2. A higher incidence of abnormal CA 19-9 level was found in Dukes’ D (100%) and Dukes’ C (84%) diseases than in Dukes’ B (76%) and Dukes’ A (75%) stages. The sensitivity of CA 19-9 in correctly detecting advanced stage CRC carcinoma from those who had early stage of the disease is (36/44) × 100 = 81.8% and its specificity in correctly excluding those who did not have advanced disease is (2/10) × 100 = 20%. The overall diagnostic accuracy is calculated to be (36 + 2)/54 = 70.37%. Regarding diagnostic values for colorectal carcinoma elevated level of serum CA 19-9 can be considered as an important diagnostic tool for differentiating advanced stage of colorectal carcinoma from its early stage TAJ 2020; 33(1): 35-40